(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2012)
The aim of the present study was to develop and evaluate orodispersible tablets of domperidone by direct compression method. Sodium starch glycolate ( SCG ), Kollidone CLSF and sodium bicarbonate were used as disintegrants to achieve the desired disintegration time required for orodispersible tablets. To mask the bitter taste of drug, impart sweetness and to offer a better feeling in mouth, saccharin sodium, aspartame, citric acid, menthol and lemon flavor were also added. Mannitol and lactose were used as sugar based multifunctional diluents. The prepared tablets were evaluated for their physical (hardness, friability, weight variation), organoleptic (taste, mouth-feel, color) and functional (disintegration time) properties and for the drug content. The excipients were used in various concentrations in order to optimize the desired properties. SCG and Kollidone CLSF, used in 5.5% and 4% respectively, gave satisfactory disintegration time using BP instrument and within the mouth. Combination of saccharin sodium (1.5%) and aspartame (3%) along with mannitol (40%) and other excipients effectively masked the bitterness and provided satisfactory sweetness level. Incorporation of 0.05% menthol provided excellent mouth feeling as assessed by a panel of volunteers. Hardness and friability values were also optimized in the formulations to produce tablets of acceptable physical stability and mechanical strength. Weight variation and drug content of all formulations fully complied with the official specifications. DOI: http://dx.doi.org/10.3329/dujps.v10i2.11791 Dhaka Univ. J. Pharm. Sci. 10(2): 117-122, 2011 (December)